2016
DOI: 10.1371/journal.pone.0155728
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength Discrimination in Drosophila Suggests a Role of Rhodopsin 1 in Color Vision

Abstract: Among the five photoreceptor opsins in the eye of Drosophila, Rhodopsin 1 (Rh1) is expressed in the six outer photoreceptors. In a previous study that combined behavioral genetics with computational modeling, we demonstrated that flies can use the signals from Rh1 for color vision. Here, we provide an in-depth computational analysis of wildtype Drosophila wavelength discrimination specifically considering the consequences of different choices of computations in the preprocessing of the behavioral data. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Functional imaging revealed no evidence for the integration of R1-R6 signals at the level of R7/R8 terminal responses (Schnaitmann et al 2018). However, a contribution of R1-R6 and of their downstream neurons L1 and L2 to color discrimination has been demonstrated in a behavioral study (Schnaitmann et al 2013;Garbers and Wachtler 2016). Therefore, the signals of R1-R6 must be integrated into the Drosophila color vision circuitry downstream of R7/ R8 terminals.…”
Section: Circuit Mechanisms Underlying Color Visionmentioning
confidence: 94%
See 1 more Smart Citation
“…Functional imaging revealed no evidence for the integration of R1-R6 signals at the level of R7/R8 terminal responses (Schnaitmann et al 2018). However, a contribution of R1-R6 and of their downstream neurons L1 and L2 to color discrimination has been demonstrated in a behavioral study (Schnaitmann et al 2013;Garbers and Wachtler 2016). Therefore, the signals of R1-R6 must be integrated into the Drosophila color vision circuitry downstream of R7/ R8 terminals.…”
Section: Circuit Mechanisms Underlying Color Visionmentioning
confidence: 94%
“…Based on their broad-band sensitivity and major role in motion vision (Heisenberg and Buchner 1977;Yamaguchi et al 2008;Wardill et al 2012), R1-R6 were thought not to contribute to fly color vision (Troje 1993). This view was challenged by the finding that Drosophila color discrimination is described best using a receptor noise-limited model that incorporates R1-R6 (Hernández de Salomon and Spatz 1983;Schnaitmann et al 2013;Garbers and Wachtler 2016). Most importantly, flies with R1-R6 and R7y as only functional photoreceptors are able to discriminate blue and green (Schnaitmann et al 2013).…”
Section: Photoreceptor Contributions To Color Visionmentioning
confidence: 99%
“…Drosophila have little perception of red-shifted light because they lack the corresponding photoreceptors (Garbers and Wachtler, 2016), so it is not surprising that they could not perceive the dark objects in this context. In addition to showing an absence of object perception in this context, these experiments indicate that the choice profiles revealed earlier are not an artifact of the maze geometry; only visible objects revealed a significant choice profile.…”
Section: Repulsion and Attraction For Different Sized Objects Remain mentioning
confidence: 99%
“…Much of what is understood about animal colour vision is derived from studies of vertebrates and only more recently have investigations revealed the neural basis of colour information processing in insects. Colour information processing in Drosophila has been investigated using behavioural experiments 10,11 , modelling 12 and by visualising neural responses directly in the fly brain, in response to light stimulation with genetic manipulation 1,2 . Colour opponency begins at the first visual synapse, the photoreceptor terminal, with reciprocal inhibition occurring between paired R7 and R8 receptors 1 .…”
Section: Introductionmentioning
confidence: 99%